SOSIALISASI KEWIRAUSAHAAN DI SMP NEGERI 01 KECAMATAN GUNUANG OMEH KABUPATEN LIMA PULUH KOTA - Weriantoni Weriantoni; Hanifatul Huda (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
Nagari Kototitinggi is one of the villages in Gunung Omeh Subdistrict, Lima Puluh Kota District, which consists of 8 jorong areas. In this Nagari. There is only one junior high school, namely SMP Negeri 01 Gunung Omeh sub-district. Here I see so much potential from adolescents that can be empowered so that later it can be useful and contribute significantly to society and the region because of the large number of teenagers there. I also see the potential of this region in Nagari Kototinggi that can be managed, so I made a work program about this entrepreneurship. Under the theme of KKN PPM Andalas University in 2019,